Stage-specific Dietary Factors Associated with the Correa Multistep and Multifactorial Process of Human Gastric Carcinogenesis. (18th May 2016) - Hsiung, Hui-Yin; Fann, Jean Ching-Yuan; Yen, Amy Ming-Fang; Chen, Sam Li-Sheng; Chiu, Sherry Yueh-Hsia; Ku, Tsung-Ho; Liu, Tzeng-Ying; Chen, Hsiu-Hsi; Lin, Ming-Wei
ABSTRACT: We assessed how individual dietary intakes act at different points in the chain of sequential stage of the Correa model in an area of Taiwan with high incidence of gastric cancer (GC). Using data on 2, 201 participants in a two-stage screening for gastric neoplasia with pepsinogen test, we identified 154 superficial gastritis (SG), 32 atrophic gastritis (AG), 117 intestinal metaplasia (IM), and 22 GC. Effects of individual item-based and construct-based dietary variables aggregated by factor analysis on each stage of gastric neoplasm were assessed. Based on 1, 211 subjects with complete information on serological test and dietary questionnaire, SG was associated with positive quartile trend for the intake of meat (trend test P = 0.0014) and the intake of fruits and leafy vegetables (trend test P = 0.0177), but with the negative trend for the intake of shrimp sauce (trend test P = 0.039). A significant positive association was noted between milk and AG (trend test P = 0.014) and IM ( P = 0.0087). A positive association between seafood and IM was noted ( P = 0.011). Frequent leafy vegetable intake based on individual item was inversely associated with GC ( P = 0.0084), whereas frequent intake of meat showed a high positive association ( P <0.001). Stage-specific dietary factors underpinning the Correa model were identified.